The role of social networking sites in the spread of boastful behavior among young people A field study on students of the Department of Sociology at Damascus University (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The research aims to study the role of social networks in the spread of boastful behavior among young people. To achieve the research objective, the descriptive analytical approach was used, a social survey with a sample, based on the scale of the role of social networks in the spread of boastful behavior among young people, which was prepared by the researchers, and distributed to a sample of (350) male and female students in the Department of Sociology at Damascus University. After collecting the data, it was analyzed on the (SPSS) program and a set of results were reached, the most important of which was that the most used sites were (Facebook, WhatsApp, Instagram, Telegram, TikTok) in order. The results also showed that the spread of boastful behavior among students of the Department of Sociology at Damascus University was high, and it was found that the most important motives for this are psychological, social and cultural motives. The results also showed that there were no statistically significant differences between the scores of the research sample members regarding the influence of social networks according to the variable (academic year, and family income level). It also showed that there were statistically significant differences according to the gender variable in favor of females, and according to the variable of place of residence in favor of the city, and the great role of networks was shown Social communication in shaping the culture of consumption and ostentation among young people and influencing their behavior, and at the end of the research, a set of proposals were presented to reduce this culture spread among young people.
Keywords: Social networking, ostentatious consumption, behavior, youth.